2020
DOI: 10.5897/ajar2020.15031
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of introduced and local cowpea genotypes performance in Botswana

Abstract: A set of twenty four cowpea (Vigna unguiculata L. Walp) genotypes were evaluated in field conditions for three consequtive seasons based on 13 quantitative characters. A combined analysis of variance revealed a highly significant difference among the genotypes for most of the traits (P <0.001). Introduced genotypes performed better in nine of the characters, revealing the advantage of introduced genotypes. Principal Component Analysis explained a total variation of 76.16%, where the first two PCs accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Generally, there was highly significant mean performance variation among clusters for the studied traits, and this is an excellent opportunity for identifying parents based on the specific traits of interest based on the future breeding objectives and improvement strategies of cowpea. Similarly, Odireleng and Bose (2020) and Yasin et al (2021) also identified cowpea genotypes based on their mean performance from the grouping of genotypes.…”
Section: Cluster Mean Performancementioning
confidence: 99%
“…Generally, there was highly significant mean performance variation among clusters for the studied traits, and this is an excellent opportunity for identifying parents based on the specific traits of interest based on the future breeding objectives and improvement strategies of cowpea. Similarly, Odireleng and Bose (2020) and Yasin et al (2021) also identified cowpea genotypes based on their mean performance from the grouping of genotypes.…”
Section: Cluster Mean Performancementioning
confidence: 99%